Evolving perspectives in Wilson dsease: diagnosis, treatment and monitoring - Weiss, Karl Heinz; Stremmel, Wolfgang (Current gastroenterology reports, 2012)
Wilson disease (WD), the autosomal recessively inherited copper overload disorder, remains a diagnostic and therapeutic challenge. In the last decade, direct sequencing of the affected gene ATP7B became commercially available, but interpretation of the results still requires careful attention. Thus, a combination of tests reflecting the disturbed copper metabolism is needed to make the final diagnosis. Because of the low disease frequency, the existing treatment concepts are not based on controlled trails. Here, recent outcome reports of larger cohort studies challenge the recommended therapies and call for individualized treatment strategies. The notion, that certain medical regimens may either be insufficient to upkeep copper homeostasis or may lead to a clinically relevant overtreatment, demand a continuous monitoring of patients even after decades of therapy. In this article, we review current diagnostic and therapeutic approaches in WD.
15 November 2011
Gesehen am 09.05.2019